(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2016)
We describe the treatment of a girl, age 18 years with Class II div-2 malocclusion with deep bite and crowding. Treatment consisted mainly of bite opening, 1st premolars extractions, canine retraction, arch co-ordination, leveling and alignment with Edgewise fixed appliances by multiloop technique. However the treatment resulted in Class I incisor relation with proper alignment of upper and lower anterior segment, an ideal overjet, overbite and incisor angulations. Ban J Orthod & Dentofac Orthop, April 2016; Vol-6 (1-2), P.29-34